2023
DOI: 10.3390/ani13040566
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Macleaya Cordata Extract on Performance, Nutrient Apparent Digestibilities, Milk Composition, and Plasma Metabolites of Dairy Goats

Abstract: In this study, we aimed to investigate the effects of Macleaya cordata extract (MCE) supplementation on performance, nutrient apparent digestibilities, plasma metabolites, and milk quality in dairy goats. Twenty-four lactating Guanzhong dairy goats (n = 24) were randomly divided into two groups (each containing 12 goats) in a 52-day trial: the CON group was fed a basal diet; the MCE group was fed a basal diet supplemented with 400 mg/kg MCE. The results indicated that the 4% fat corrected milk yield (4% FCM); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The macleaya extract (MCE) contains sanguinarine and chelerythrine, which possess anti-inflammatory, antioxidant, bactericidal, and anti-tumor properties (4). Accordingly, MCE plays roles in improving animal immunity and animal growth, and preserving intestinal health (5). Studies have shown that macleaya extract can improve the growth performance, antioxidant capacity, and immune function of piglets (6,7) and broiler chickens (8).…”
Section: Introductionmentioning
confidence: 99%
“…The macleaya extract (MCE) contains sanguinarine and chelerythrine, which possess anti-inflammatory, antioxidant, bactericidal, and anti-tumor properties (4). Accordingly, MCE plays roles in improving animal immunity and animal growth, and preserving intestinal health (5). Studies have shown that macleaya extract can improve the growth performance, antioxidant capacity, and immune function of piglets (6,7) and broiler chickens (8).…”
Section: Introductionmentioning
confidence: 99%